Karakteristik Pasien pada Kondisi Obesitas yang Berumur diatas 40 Tahun - Anugrah, Iqra; Makmun, Armanto (Indonesian Journal of Health, 2024)
Obesity is an abnormal accumulation of fat and is usually categorized as an increase of 20% from ideal body weight or a body mass index above 25. WHO reported that in 2016, more than 1.9 billion adults, aged 18 years and over, were overweight and complicated by other diseases. The purpose of this study was to determine the characteristics of obese patients aged over 40 years at the Tamangapa Health Center in Makassar City. The research method used was descriptive research to determine the characteristics of obese patients aged over 40 years at the Tamangapa Health Center in Makassar. The results of this study showed that obese patients were female as many as 39 patients (65%) and male patients 21 patients (35%). Based on age, patients with the age group 40-59 years numbered 37 people (61.6%), the age group 60-74 years numbered 19 people (31.7%), the age group 75-90 years numbered 4 people (6.7%). Based on the disease, patients with hypertension were 45 people (38.8%), diabetes mellitus were 18 people (15.5%), LBP were 10 people (8.6%), myocardial infarction and hypercholesterolemia were 9 people (7.8%), osteoarthritis were 7 people (6%), gout arthritis and stroke were 5 people (4.3%), breast cancer were 3 people (2.6%), asthma and prostate disorders were 2 people (1.7%), and endometrial cysts were 1 person (0.9%). The conclusion of the study was that women were more obese than men, from the age of the patients, it was found that the age group of 40-59 years was more obese, followed by patients aged 60-74 years. Based on the diseases suffered by obese patients, the majority of patients suffered from hypertension and diabetes mellitus while the least suffered from endometrial cysts.